Treatment of Tapis A oil-contaminated sediment by using a dual-stage biodegradation - Hii, Yii-Siang; Ah , Theem Law (Penerbit Universiti Sains Malaysia, 2004)
Malaysian marine environment is vulnerable to oil pollution, especially in the Straits of Malacca (Law et al., 2002). Busy maritime transports, active oil explorations and increases industrial activities are the primary factors that lead to oil pollution in the aquatic environment. When oil intruded into the environment, sediment acts as the final “sink” for the pollutants. Oily sediment may pose long term hazardous effects on a wide spectrum of organisms.